ANALISIS TINGKAT PEMAHAMAN MAHASISWA ILMU KOMPUTER PADA JENIS PARAGRAF - Tasya Aulia Fitri; Sazwani Ardhia Sahira; Nabil Nailul Abrar; Risya Sahdaini Br. Sembiring; Dila Handayani (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to determine the level of understanding of students from the Computer Science Study Program at the State Islamic University of North Sumatra (UINSU) regarding types of paragraphs in the Indonesian language. The research employed a quantitative approach using questionnaires and descriptive analysis. The results show that persuasive (40.5%) and argumentative (35.1%) paragraphs are the most difficult for students to understand, while expository, descriptive, and narrative paragraphs are relatively easier. These findings indicate that non-language students experience difficulties with paragraph types that require reasoning and systematic argument construction, highlighting the need for more effective Indonesian language learning strategies